Finametric Determinant of Insurance Profitability: Analysis of the Nigerian Experience - Ezirim, Chinedu B; Ezirim, Ucheoma I; Eniekezimene, Daniel; Elike, Uchenna (Archives of Business Research, 2017)
The study set out to finametrically investigate the key determinants of insurance profitability in Nigeria using least squares and associated diagnostic tests, co-integration, and the fully modified Phillips-Hansen estimation procedures. The results indicate that five variables namely premium ratio, level of economic activity (or simply, state of the economy), and investment ratio, and profitability in previous periods significantly and positively influenced current profitability of insurance companies in Nigeria. Only financial market conditions and claims ratio were found to exert significant but negative influence on current profitability. There also existed long-run equilibrium relationship between the variables such that the observed influences are likely to persist in the long-run, ceteris paribus.